PHQ-9 Response Curve - Kurt B. Angstman; James E. Rohrer; Norman H. Rasmussen (SAGE Publishing, 2012)
Major depressive disorder is common in primary care. Depression Improvement Across Minnesota-Offering a New Direction (DIAMOND), using a collaborative care model, was first implemented in March 2008 starting with 5 clinics and expanding to more than 70 clinics statewide by 2010. This was intended to improve depression management and to augment the relationship between the patient, the primary care provider, and the psychiatrist. Prior retrospective studies have demonstrated the clinical effectiveness of our program. This study was designed to examine those patients who were in clinical remission (defined as a Patient Health Questionnaire-9 [PHQ-9] score <5) at 6 months (180 days) after enrollment in collaborative care management. By determining the subsequent PHQ-9 data that were obtained, a PHQ-9 response curve was developed for those patients who did improve. The pilot study demonstrated that there appeared to be rapid response to depression treatment, evident by the first month of treatment and more pronounced in severely depressed patients. Also, it demonstrated that in the patients who did respond, there was no any difference in the remission rates over the study period when evaluated by the initial severity of the depression.